2017
DOI: 10.1002/joc.4981
|View full text |Cite
|
Sign up to set email alerts
|

Removing the relocation bias from the 155‐year Haparanda temperature record in Northern Europe

Abstract: The village Haparanda in northern Sweden hosts one of the longest meteorological station records in Europe depicting climate conditions in the subarctic. Since the station was relocated several times, moving gradually from urbanized to more rural areas, the record is likely biased by anthropogenic influences. We here assess these influences and demonstrate that even in villages urban heat island biases might affect the temperature readings. We detail a method to quantify this bias and remove it from the long H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Potential reasons for this discrepancy in the low-frequency domain include (i) a nonlinearity or decoupling of the growth/climate response on longer time scales (Fritts 1976); (ii) the more white precipitation spectrum compared to the red temperature spectrum (Ault & St. George 2010); (iii) potential biases in longterm trends inherent to instrumental data, e.g. caused by station relocations or changes in their operating system (Dienst et al 2017); and (iv) the difficulty in preserving low-frequency variance in TRW (Esper et al 2002). As also the reliable instrumental target extends only over 55 years back to 1961, the full spectrum of potential SPI variability, and particularly the low-frequency end of that spectrum over longer time scales remains unaddressed.…”
Section: Hydro-climatic Signalmentioning
confidence: 99%
“…Potential reasons for this discrepancy in the low-frequency domain include (i) a nonlinearity or decoupling of the growth/climate response on longer time scales (Fritts 1976); (ii) the more white precipitation spectrum compared to the red temperature spectrum (Ault & St. George 2010); (iii) potential biases in longterm trends inherent to instrumental data, e.g. caused by station relocations or changes in their operating system (Dienst et al 2017); and (iv) the difficulty in preserving low-frequency variance in TRW (Esper et al 2002). As also the reliable instrumental target extends only over 55 years back to 1961, the full spectrum of potential SPI variability, and particularly the low-frequency end of that spectrum over longer time scales remains unaddressed.…”
Section: Hydro-climatic Signalmentioning
confidence: 99%
“…HOMER has been widely used for the homogenization of different climatological variables. More than 30 published papers (to the best of our knowledge) have mentioned the use of this software for the homogenization of different variables such as air temperature (e.g., Mamara et al ., ; Dienst et al ., ), precipitation (e.g., Coll et al ., ; Noone et al ., ; Prohom et al ., ) and wind speed (e.g., Laapas and Venäläinen, ). In our study, we applied a two‐cycle process, as suggested in Mestre and Aguilar ().…”
Section: Methodsmentioning
confidence: 99%
“…A network of temperature sensors was established in each village and its surroundings ( Fig. 1), originally to detect the urban warming effect on historical temperature measurements (Lindén et al 2015b, Dienst et al 2017. We closely followed the WMO guidelines for sensor installation in urban climate studies (WMO 2008), though a completely standardized placement, e.g.…”
Section: Temperature Sensor Networkmentioning
confidence: 99%
“…Therefore, ap proaches to homogenize temperature data have be come vital to ensure their reliability (Brunet et al 2006, Venema et al 2012. Albeit aiming at re moving all non-climatic impact in the temperature data, homo genization and correction of time series might as well have inadvertent implications, like the recovery of urban warming bias (Zhang et al 2014, Dienst et al 2017, emphasizing the need to adjust records with special diligence. Cities contain the highest potential to affect the representativity of meteorological station measurements due to their large extension, but even smaller towns and villages influence the observations.…”
Section: Introductionmentioning
confidence: 99%